Synthesis, biological evaluation and molecular docking of novel coumarin incorporated triazoles as antitubercular, antioxidant and antimicrobial agents - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Shingate, Bapurao B.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Khedkar, Vijay M.; Nawale, Laxman; Sarkar, Dhiman; Navale, Govinda R.; Shinde, Sandip S. (Medicinal Chemistry Research, 2016)
A series of new coumarin-based 1,2,3-triazole derivatives were designed, synthesized and evaluated for their antitubercular activity in vitro against Mycobacterium tuberculosis H37Ra, antioxidant activity by DPPH radical scavenging assay, antimicrobial activity in vitro against three gram-positive bacteria (Staphylococcus aureus, Micrococcus luteus and Bacillus cereus) and three gram-negative bacteria (Escherichia coli, Pseudomonas fluorescens and Flavobacterium devorans as well as three fungi (Aspergillus niger, Penicillium chrysogenum and Curvularia lunata). The bioactive assay showed that some synthesized coumarin triazoles displayed comparable or even better antitubercular, antioxidant, antibacterial and antifungal efficacy in comparison with reference drugs. Furthermore, docking study has been performed against DprE1 enzyme of M. tuberculosis that showed good binding interactions. Moreover, the synthesized compounds were also analyzed for ADME properties and showed potential to build up as good oral drug candidates. New coumarin-based 1,2,3-triazole derivatives were designed, synthesized and evaluated for their antitubercular, antioxidant, antibacterial and antifungal activity. Some of the coumarin-based triazole derivatives displayed comparable or even better efficacy in comparison with reference drugs. Molecular docking study has been performed against DprE1 enzyme of Mycobacterium tuberculosis showed good binding interactions. [GRAPHICS] .
Keywords: 1; 2; 3-Triazole; ADME prediction; Antimicrobial; Antioxidant; Antitubercular; Click chemistry; Docking study

Synthesis of novel triazole-incorporated isatin derivatives as antifungal, antitubercular, and antioxidant agents and molecular docking study - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Nawale, Laxman; Arkile, Manisha A.; Sarkar, Dhiman; Shingate, Bapurao B. (Journal of Heterocyclic Chemistry, 2017)
A library of 1,2,3-triazoles efficiently prepared via click chemistry and evaluated for their antifungal, antitubercular, antioxidant, cytotoxicity, molecular docking and ADME prediction.

Synthesis and biological evaluation of novel triazole-biscoumarin conjugates as potential antitubercular and anti-oxidant agents - Danne, Ashruba B. (Research on Chemical Intermediates, 2018)
The synthesis of a new series of triazole-biscoumarin conjugates by using a molecular hybridization approach is described. The newly synthesized compounds 6a–k were evaluated for their in vitro antitubercular activity against active and dormant Mtb H37Ra and anti-oxidant activity against DPPH radical scavenging. Molecular docking simulations for the antitubercular activity showed that the conjugates 6a–k bind in the pocket of the DprE1 enzyme. Most of the conjugates displayed good antitubercular activity against both the active and dormant Mtb H37Ra strain. The compound 6h displayed very good antitubercular activity against dormant Mtb H37Ra with an IC50 value of 1.44 μg/mL. Most of the synthesized conjugates exhibit excellent anti-oxidant activity with an IC50 of less than the standard BHT. Compound 6b is the most active among all the conjugates with an IC50 value of 08.17 ± 0.11 μg/mL. The molecular docking study shows good agreement between the observed antitubercular activity and the binding affinity.
Keywords: 1; 2; 3-triazoles; Anti-oxidant activity; Antitubercular activity; Biscoumarins; Molecular docking

Synthesis of novel alpha-aminophosphonate derivatives, biological evaluation as potent antiproliferative agents and molecular docking - Deshmukh, Satish U. (ChemistrySelect, 2018)
A series of novel fluorine containing α‐aminophosphonate derivatives (4 a–4 q) were synthesized in excellent yield and high purity. All these novel Fluorinated α‐aminophosphonate compounds were screened for antiproliferative and apoptosis activity on human non small cell lung carcinoma cells (A549) and human skin melanoma cells (SK‐MEL‐2). Compounds 4 a, 4 b, 4 c, 4 f, 4 i, 4 j and 4 m were found to be more active antiproliferative agent against A549 and SK‐MEL‐2 cells with IC50 value 0.22 to 1.25 μM. Molecular docking study related to binding affinity and binding mode analysis showed that synthesized compounds had potential to inhibit human Topoisomerase IIa enzyme system. Flow cytometric study showed some of these derivatives also induced cell apoptosis and arrest cell cycle at G1 and at G2/M phase. Overall, this study provides future perspective of lead candidate for the future anticancer drug discovery initiatives.